Meningkatkan Pengetahuan Orang Tua tentang Pemberdayaan Keluarga dalam Upaya Pengasuhan Anak dengan Kegiatan "BELAJAR DI RUMAHANAKKU” - NLP Yunianti Suntari; Ni Luh Kompyang Sulisnadewi; I Ketut Labir (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2023)
Efforts to produce quality healthy and intelligent children are a priority for the national development program. In achieving this goal, of course, requires the involvement of many parties. The strategic thing is to empower families to be able to provide and carry out optimal and proper parenting for their children. So far, toddler development monitoring services have been carried out at Posyandu. The quality of services at Posyandu can be improved by involving families/parents in it, with the family empowerment movement. Purpose: Optimizing parental guidance for children in their growth period. To help emotional maturity and independence in facing life by applying proper parenting. Method: Mechanism of community service actifities (1) We introduces ourselves to the person in charge, cadre, parents of toddlers at the Posyandu, conveys information, explains the purpose and procedure of “Studying at My Children’s Home.” (2) Conduct a pre test to asses parental knowledge about family empowerment in child rearing efforts. (3) Carrying out educational/health counseling interventions regarding parental knowledge about family empowermwnt in children efforts, packaged with “Studying at My Children’s Home” activities. (4) Carrying out a post test after the intervention. (5) Analyzing data. Results: From 140 respondents, 93 people or 66.43% got good benefits. 37 people or 26.43% got sufficient benefits, and 10 people or 7.14% did not get significant benefits from “Studying at My Children’s Home” activity. Conclusion: The “Studying at My Children’s Home” activity gives a new situation to the counseling method in society or the community. With 3 (three) main activities (1) modeling/give examples (2) Repetition and (3) Reinforcement/strengthening for something good. At the end of this community service activity, it was generally found and increase in family understanding and empowerment in childcare.